Predictive Power of Incidents Reporting Rate and Its Dimensions by Job Stress among Workers' Isfahan Steel Company - F Kiani; H Samavatyan; S Pourabdian; E Jafari (Tehran University of Medical Sciences, 2011)
Background: There is long-term interest in the effects of stress on health, due to the strain that it places on individuals which can lead to an increased risk of disease. The present study examined degree of perceived job stress related to incidents reporting rate and its dimensions among workers' Isfahan Steel Company.Methods: A self-administered anonymous was distributed to 189 workers. The survey included demographic factors, incidents reporting rate and its components (physical symptoms, psychological symptoms and accidents) and the Job Stress Questionnaire. The data were analyzed by multivariate (MANOVA) and correlation techniques.Results: 1) there was internal significant correlation between perceived job stress with incident reporting rate as well as with its two components namely physical symptoms and psychological symptoms; 2) there was not a significant relationship between perceived job stress and accident; 2) In multivariate analysis, perceived job stress respectively about 12%, 18% and 19% of the variance of variables of incidents reporting rate, physical and psychological symptoms significantly predicted (P< 0.05).Conclusion: Perceived job stress influences to physical and psychological symptoms. Therefore, decreasing job stress can be important to prevent the development of stress-related diseases and to promote workers health.